Reflections on training and teaching modes for anesthesia monitoring nurses in China - Han Yu; Cao Zhang; Jiangqin He; Jianhong Xu (Heliyon, 2024)
Objective: The purpose of this scoping review was to map and identify studies describing the current state of research and teaching methods and evaluation systems for nurse anesthetists within China. Design: A wide-ranging search of multiple databases and gray literature was performed according to JBI criteria, employing predefined selection criteria and following PRISMA guidelines. Methods: This scoping review included studies published between 1988 and 2021 that explored the current state of clinical training and teaching methods for nurse anesthetists nationally and internationally. These articles were reviewed by four reviewers and content analysis was performed. Results: Fifty-two articles were included in the review. The results suggest that both simulation teaching in nursing education and Kolb's experiential learning cycle theory improve nursing staff teamwork, develop critical thinking skills, and improve core nursing competencies. Conclusions: High-fidelity simulation teaching based on Kolb's experiential learning cycle theory may be an effective teaching method to develop and improve the competence of nurse anesthesia monitors.